The central bank digital currency in malaysia : A literature review - Normi Sham, Awang Abu Bakar; Norzariyah, Yahya; Irni Eliana, Khairuddin; Ahmad Firdaus, Zainal Abidin; Jasni, Mohamad Zain; Norbik Bashah, Idris (Springer Science and Business Media Deutschland GmbH, 2023)
Central Bank Digital Currency (CBDC) is a digital form of central bank money, and is different from traditional reserves or settlement accounts balances. In line with the digital technology era, CBDC has gained interest among the majority of the countries. Central banks in a number of countries have started experimenting, piloting, launching, and have laid their direction on CBDC. However, the development of CBDC in Malaysia is still behind compared to many other countries in the world. This paper aims to present the current status of CBDC in Malaysia. To achieve the goal, this paper explores literature reviews on CBDC, countries’ milestones on CBDC and Malaysia’s Central Bank stand on CBDC. This review found that Malaysia’s Central Bank has no intention for the immediate plan for CBDC in Malaysia. However, Malaysia’s Central Bank continues assessing the CBDC potential, especially in the digital assets and payments space. This study also found that Malaysia’s Central Bank participated in a cross-border payments trial under Project Dunbar.